Mental Health Changes in Older Adults in Response to the COVID-19 Pandemic: A Longitudinal Study in Mexico - Betancourt-Ocampo, Diana; Toledo-Fernández, Aldebarán; González-González, Alejandro (Frontiers in Public Health, 2022)
This study examined changes in some aspects of mental health, as well as worries and behaviors related to the COVID-19 pandemic in a sample of older adults, during three different moments of the first year of the pandemic in Mexico. The sample consisted of 2,307 older adults (38% men and 62% women). The results indicated that older adults presented less concern about the COVID-19 pandemic, as well as less adherence to preventing procedures in the first wave, compared to subsequent evaluations. In addition, greater depressive symptoms, anxiety and stress were found in older adults in the last wave; however, the proportion of older adults identified with high scores in these variables was lower than that reported in national data.